Highland destiny - Howell, Hannah (Howell, Hannah. Murrays., 2022)
Driven by rage and heartbreak, Caitlin MacLeod, the daughter of a powerful Scottish chieftain, searches for the man who betrayed her and stole her clan's most priceless treasure-a man who is now desperate to get back into her good graces.